The economics of Integrated Multi‐Trophic Aquaculture: where are we now and where do we need to go?. (27th January 2020) - Knowler, Duncan; Chopin, Thierry; Martínez‐Espiñeira, Rober; Neori, Amir; Nobre, Ana; Noce, Anthony; Reid, Gregor
Abstract: In integrated multi‐trophic aquaculture (IMTA), species from different trophic levels are raised in proximity to one another and the co‐products (organic and inorganic wastes) of one cultured species are recycled to serve as nutritional inputs for others. IMTA can reduce the ecological impacts near aquaculture operations, improve social perceptions of aquaculture and provide financial benefits for aquaculture producers via product diversification, faster production cycles and price premiums on IMTA products. We review aspects of IMTA's economic potential and market acceptance and consider ways to address the current gaps in our understanding. We find that adopting IMTA raises the assimilative capacity of the farm and that IMTA substantively reduces the environmental cost of aquaculture. Moreover, integrating extractive species (e.g. invertebrates and/or seaweeds), with existing fed‐monoculture operations, can increase farm profits. The presence of positive public attitudes towards IMTA, as expressed by a willingness to pay a premium for its products, can further increase the profitability of adopting IMTA. Areas requiring more economic research include the development of comparative bioeconomic models of IMTA and the evaluation of competing production systems and their ability to internalize externalities to demonstrate the true value of IMTA to society. Further exploration of economic incentives, such as instruments needed to foster adoption of IMTA, and investigation of marketing opportunities, such as promoting the eco‐certification of IMTA products, are also needed. Our paper aimed to inform economists and non‐economists alike about the latest developments in IMTA economics, and spur further research on critical topics concerning this important subject.